2020
DOI: 10.1016/j.ijid.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling strongyloidiasis risk in the United States

Abstract: To provide a spatial risk assessment for the neglected disease strongyloidiasis in the United States by prioritizing areas with high probability of Strongyloides stercoralis presence and to offer recommendations for targeted screening and surveillance. Methods: The risk assessment was based on a species distribution model with parasite occurrence data and ecologically important environmental variables as input and local habitat suitability for the species as output. The model used a maximum entropy algorithm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Our knowledge of the geographic distribution of Strongyloides species globally is limited, even in high-income country (HIC) settings. For example, recent modeling suggests far larger areas in the United States provide a suitable habitat for Strongyloides than previously described [ 36 ], consistent with previous reports of strongyloidiasis without travel to areas of higher endemicity [ 37 ]. A recent study performed in rural Alabama found a 7.3% prevalence of S. stercoralis using stool PCR analysis [ 38 ], which is higher than that of previous studies which used less sensitive stool microscopy detection methods [ 39 ].…”
Section: Risk Factors For Shs In Covid-19supporting
confidence: 85%
“…Our knowledge of the geographic distribution of Strongyloides species globally is limited, even in high-income country (HIC) settings. For example, recent modeling suggests far larger areas in the United States provide a suitable habitat for Strongyloides than previously described [ 36 ], consistent with previous reports of strongyloidiasis without travel to areas of higher endemicity [ 37 ]. A recent study performed in rural Alabama found a 7.3% prevalence of S. stercoralis using stool PCR analysis [ 38 ], which is higher than that of previous studies which used less sensitive stool microscopy detection methods [ 39 ].…”
Section: Risk Factors For Shs In Covid-19supporting
confidence: 85%
“…Strongyloidiasis is a worldwide helminthiasis that is highly prevalent in tropical or subtropical countries [ 37 ]. Additionally, endemic pockets have been recorded in more temperate areas, such as the Southeastern states of the USA [ 38 ] or Southern Europe [ 39 ]. Concerning France, the presence of autochthonous strongyloidiasis in the Midi-Pyrénées Region had been previously reported [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, do not go barefoot when traveling in fields, and wash raw vegetables and fruit thoroughly. 20 Patients receiving long-term steroids should also take prophylactic medication (albendazole) every three months to prevent strongyloidiasis. 9 …”
Section: Discussionmentioning
confidence: 99%